2013
DOI: 10.1271/bbb.130019
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by DietaryD-Psicose of Body Fat Accumulation in Adult Rats Fed a High-Sucrose Diet

Abstract: We investigated the anti-obesity effects of dietary D-psicose on adult rats fed a high-sucrose diet. Wistar rats (16 weeks old) that had previously been fed a high-sucrose diet (HSD) were fed HSD or a high-starch diet (HTD) with or without 5% D-psicose for 8 weeks. The food efficiency, carcass fat percentage, abdominal fat accumulation, and body weight gain were all significantly suppressed by dietary D-psicose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 24 publications
1
55
0
Order By: Relevance
“…D-Allulose might partially inhibit the uptake of D-glucose and/or D-fructose at GLUT2 or GLUT5 in those tissues and cells. The suppressive effect of the non-metabolized sugar D-allulose on the uptake of D-glucose and D-fructose might contribute to the important biological functions of D-allulose, such as the improvement of insulin resistance and the inhibition of body fat accumulation (Hossain et al, 2011;Ochiai et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…D-Allulose might partially inhibit the uptake of D-glucose and/or D-fructose at GLUT2 or GLUT5 in those tissues and cells. The suppressive effect of the non-metabolized sugar D-allulose on the uptake of D-glucose and D-fructose might contribute to the important biological functions of D-allulose, such as the improvement of insulin resistance and the inhibition of body fat accumulation (Hossain et al, 2011;Ochiai et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The rare sugar d-psicose is the C-3 epimer of d-fructose, has 70% of relative sweetness but only 0.3% of energy of sucrose [8,9], and has been approved as Generally Regarded as Safe (GRAS) by U.S. Food and Drug Administration (DFA). It has enormous physiological benefits including blood glucose suppressive property [10], neuroprotective effect [11], reactive oxygen species scavenging activity [12], and anti-obesity effect [13,14]. In addition, d-psicose has been considered to be able to improve food quality, for examples, it increases the gelling property and produces higher antioxidant activity and pleasant flavor through Maillard reaction with food proteins [15], and it facilitates melting of the crystalline structure in rice flour upon heating and inhibits re-crystallization during http storage [16].…”
Section: Introductionmentioning
confidence: 99%
“…In animal studies investigating the anti-obesity effects of d-allulose, d-allulose content in the diet was mainly set at the level of 3% (27) or 5% (11,12,15,28), although the carbohydrate source in the diets and the animal model varied depending on studies. Our previous study (28) reported that a 5% d-allulose diet for 8 wk significantly suppressed body fat accumulation and increased energy expenditure in rats fed a sucrose-based diet.…”
Section: Resultsmentioning
confidence: 99%
“…The levels of hepatic TG and cholesterol were measured as described in serum analyses. The fat contents of the carcass and total body were measured and calculated as described previously (12). Briefly, a carcass sample softened by autoclave treatment (121˚C, 90 min) was ground using a food mixer, and debris of bone was fully removed in order to obtain a carcass meat sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation